(untitled) (Journal of Hama University, 2025)
In this paper, we provide a review of the necessity of analyzing government data and the challenges it faces, whether at the local or international levels. In doing so, we used peer-reviewed articles, reports from international organizations, direct information from government employees, and electronic sources for government initiatives. The goal of this review is to draw the attention of decision makers to the importance of analyzing government data, as it is one of the emerging topics necessary to achieve sustainable development and good governance. In this article, we reviewed some cases that demonstrate the importance of data analysis in governance, development, and responding to emergency cases. We discussed the technical and logistical challenges. We reviewed the reality of data analysis in world governments. We focused on the reality of the national experience, then moved on to review the best artificial intelligence techniques that can be adapted to analyzing government data, and finally, we concluded the review with a number of recommendations.